Nurses’ educational role in the prevention of complications among patients with type 2 diabetes mellitus - Santalia Banne Tondok; Wibowo Hanafi Ari Susanto; Suningsih Suabey; I Ketut Swastikaa (Edukasi Ilmiah Indonesia, 2025)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a chronic disease with a high risk of long-term complications that significantly affect patients’ quality of life and healthcare costs. Despite advances in medical management, complication rates remain high, indicating the need for effective educational interventions. Nurses play a pivotal role in diabetes education, yet evidence focusing on their specific contribution to complication prevention remains limited. Methods: This quantitative, descriptive-analytic cross-sectional study involved 50 patients with T2DM selected through purposive sampling. Data were collected using validated questionnaires that measured nurses’ educational roles and patients’ complication-prevention behaviors. Univariate analysis described respondent characteristics and study variables, while bivariate analysis using the chi-square test examined the relationship between nurses’ educational roles and complication prevention. Results: Most respondents perceived nurses’ educational roles as good (64%) and demonstrated good complication prevention behaviors (60%). Bivariate analysis showed a statistically significant relationship between nurses’ educational roles and prevention of complications (?² = 14.62; p = 0.002). Patients who received higher-quality nurse-led education were more likely to engage in effective preventive behaviors. The findings indicate that strong nurse-led educational support is associated with better preventive practices among patients with T2DM. Nurses’ consistent, patient-centered education plays a critical role in enhancing self-care behaviors and reducing the risk of diabetes-related complications. Conclusion: Nurses’ educational roles significantly contribute to the prevention of complications in patients with Type 2 Diabetes Mellitus. Strengthening structured nurse-led education should be prioritized to improve long-term diabetes outcomes